A Novel Electrochemical Method for Protionamide Determination Based on Its Interaction with Alizarin Red S. (30th August 2015) - Zhang, Weili; Niu, Xueliang; Zhang, Hua; Jiang, Qingqing; Zhang, Pingping
Abstract : The interaction of protionamide with alizarin red S (ARS) and its analytical application were carefully investigated in this contribution. The interaction conditions were carefully studied and optimized by cyclic voltammetry. Under the optimum conditions, the cyclic voltammetry curve of ARS showed an oxidation peak with the peak potential of 0.57 V. After the addition of protionamide to the ARS solution, the peak potential was negatively moved, and meanwhile the oxidation peak current decreased apparently to the concentration of protionamide and then a new method for the protionamide determination was established. The linear equation between the decreasing current (Δip) and protionamide concentration was got as Δip ( μ A) = 0.01514C (mg/L) −0.01553  ( n = 9 ;   r = 0.991 ) with the linear range of 10.0~50.0 mg/L, and the detection limit (3σ ) was got as 8.25  μ g/mL. The effects of coexisting substances on the determination were carefully investigated and the protionamide artificial and tablet samples were detected with satisfactory results.